Assessing the Impact of Reservoir Water Availability on Clean Water Quality - Risnawati, Risnawati; Sidabutar, Yuanita FD; Silalahi, Ratna Dewi; Sarmini, Sarmini (Journal La Lifesci, 2024)
This paper aims to explore the key issues that govern water resource management in a particular District of East Tanjungpinang in Indonesia with particular reference to the reservoir systems on which the District relies heavily especially during the rainy seasons. Using both statistical analysis of water quality data and case-study / interview data, this research demonstrates that the district is exposed to climate variability, increasingly inadequate water infrastructure, and pollution threats. The research study shows that the reduction in water levels is being accompanied by poor water quality both due to poor infrastructure and increased pollution from industrial, agricultural and domestic sectors. The study provides new directions for water management, it emphasizes the need for enhanced more adaptive and resilient water management approaches that include technologies, infrastructure and green infrastructure. This also raises the call to develop better governance systems that increase opportunities for people’s participation, better compliance with the law, and the incorporation of indigenous concepts with contemporary management systems. Overall, it advances the understanding of water security concept and provides findings and suggestions for other regions in the world experiencing the same issues in the management of the freshwater resources under the conditions of climate change and growing urbanization.